Review on space science research in Malaysia - Zainuddin, Mohd Zambri; Abdullah, Mardina; Abidin, Zamri Zainal; Bahari, Siti Aminah; Asillam, Mhd Fairos; Hashim, Mohd Helmy; Radzi, Zahira Mohd (Akademi Sains Malaysia, 2019)
The Malaysia in space science R & D is still in its infancy stage. Internationally, space science has a major role and has impacted our society over the last 50 years and will continue providing returns on investment. The Return on Investment (ROI) could be in the form of new knowledge that provides understanding to world problems such as those relating to the Earth-Sun relationship. These can be directly or indirectly beneficial. The main output from space science R & D is new knowledge which is "priceless". Other than that space science will provide economic opportunities as well as wealth creation and social well-being. In Malaysia, space science R & D has progressed but there are a lot of windows for improvement. This review article looked at several milestones in the Malaysian space science R & D program as well as at its current challenges. Recommendations are made for the improvement of the space science R & D program in Malaysia.